WHEN I EMBODIED THE TRACE OF THE TRUE BANDIT. ROTOS BANDIDOS IN THE CHILEAN LITERATURE - Rojas Sotoconil, Araucaria (Revista de Historia Social y de las Mentalidades, 2012)
The following article seeks to reconsider the discourses articulated around the “bandidaje” from the field of literature in Chile. Some of the questions explored are: How is a bandido perceived by an external observer? Or, Is there any coincidence between the bandido established by historiography and the one created by literary texts? In this sense, special attention is paid to the links between different figures, namely the peón-gañán, roto chileno and bandido, exploring also the symbolic rupture implied in the practice of bandidaje. Considering misfortune as a transversal background, this essay exposes the motives urging the bandido to become a bandit. People’s poetry, romances, cuecas, tales and novels - laid out on an extended temporal framework - guide the analysis, organized in terms of their subjects rather than the chronology, in order to emphasizes certain commonly used layouts in the configuration of the imagery of the bandido.